2013
DOI: 10.1007/s00572-013-0493-z
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the ectomycorrhizal community in a declining Quercus suber L. stand

Abstract: This survey was carried out in a Quercus suber L. stand with many trees affected by the disease "oak decline". Its aim was to obtain information about both the belowground ectomycorrhizal fungal community in a declining Q. suber stand as a whole, and the ectomycorrhizal fungal community of individual tree (EFT) detected in healthy and diseased plants. To this end, we first categorized the trees into four different decline classes (one for healthy plants and three for diseased plants) and then, by using morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
2
19
2
Order By: Relevance
“…The ECM fungal community associated with cork oaks was mainly represented by Russula (29%), Tomentella (20%), and Cenoccoccum (10%), which is in accordance with other reports on Q. suber forests that also describe a highly enriched ECMF community with C. geophilum, Russulaceae, and Thelephoraceae (Yakhlef et al 2009;Azul et al 2010;Lancellotti and Franceschini 2013;Maghnia et al 2017). This trend is commonly seen in other Fagaceae forests (reviewed by Reis et al (2017)).…”
Section: Ecmf Community Associated With Cork Oak In Different Landscapessupporting
confidence: 80%
See 1 more Smart Citation
“…The ECM fungal community associated with cork oaks was mainly represented by Russula (29%), Tomentella (20%), and Cenoccoccum (10%), which is in accordance with other reports on Q. suber forests that also describe a highly enriched ECMF community with C. geophilum, Russulaceae, and Thelephoraceae (Yakhlef et al 2009;Azul et al 2010;Lancellotti and Franceschini 2013;Maghnia et al 2017). This trend is commonly seen in other Fagaceae forests (reviewed by Reis et al (2017)).…”
Section: Ecmf Community Associated With Cork Oak In Different Landscapessupporting
confidence: 80%
“…The main drivers of ECMF also include abiotic conditions, climatic factors (Mucha et al 2018), and soil properties (Albornoz et al 2016) or soil resources (Courty et al 2016). The diversity and structure of Quercus ECMF communities have already been studied based on the ITS barcoding of ECM tips (Smith and Read 2008;Azul et al 2010;Shi et al 2011;Richard et al 2011;Lancellotti and Franceschini 2013). The ECMF richness in cork oak montados was previously correlated with landscape and land use practices, but only cork oak forests situated on arid/semi-arid region climates were used (Azul et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of oak decline disease, a reduction of ECM diversity and ECM root colonization has been detected in Q. ilex trees (Causin 1996;Montecchio et al 2004). In contrast, Q. suber declined trees do not present differences in ECM community when compared to healthy trees (Lancellotti and Franceschini 2013). But, although no differences in ECM community have been detected in Spanish Q. ilex forest trees infected or not with P. cinnamomi, non-mycorrhizal root tips seem to be more susceptible to infection than mycorrhizal ones (Corcobado et al 2014).…”
Section: Disturbance and Protection Of Fagaceae Forests From Biotic Tmentioning
confidence: 65%
“…Such a general decrease in tree health and cover has a large potential to impact mycorrhizal communities, but this issue remains largely unexplored. The few studies that have assessed the effect of tree dieback on mycorrhizas have shown that mycorrhizal communities in the roots of declining trees can differ in type, abundance and/or composition compared with those found in healthy trees (Perrin and Estivalet, 1989;Causin et al, 1996;Montecchio et al, 2004;Ishaq et al, 2013;Lancellotti and Franceschini, 2013). Defoliation might negatively affect mycorrhizal fungi through C allocation to roots, since the progressive loss of photosynthetic area in declining trees could translate into a reduction of the amount of soluble carbohydrates delivered to the symbiotic fungal partners (Gehring and Whitham, 2003;Druebert et al, 2009).…”
Section: Introductionmentioning
confidence: 98%